2004
DOI: 10.2135/cropsci2004.5010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Uptake and Distribution of Cadmium in Different Cultivars of Bread and Durum Wheat

Abstract: Cd from soil is dependent on the Cd concentration in the soil, the soil pH, and the level of organic matter The intent of this study was to investigate whether high levels of and zinc in the soil (Eriksson et al., 1996; Eriksson and cadmium (Cd) in the grains of high Cd-accumulating cultivars is caused by a high Cd uptake in the roots, a high translocation of Cd from Sö derströ m, 1996). While these soil factors mainly reguroots to shoot, or a redistribution of Cd between the shoot and the late the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(86 citation statements)
references
References 14 publications
8
76
1
1
Order By: Relevance
“…All the samples respected the legal regulations of Spain. Herce-Pagliai et al 22 found arsenic at a level of 1.5-12.4 μg/L. No differences were found between bottled and canned beers, as well as no correlation existed with the specific gravity of the beers 9 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…All the samples respected the legal regulations of Spain. Herce-Pagliai et al 22 found arsenic at a level of 1.5-12.4 μg/L. No differences were found between bottled and canned beers, as well as no correlation existed with the specific gravity of the beers 9 .…”
Section: Resultsmentioning
confidence: 94%
“…The process employed in the production of alcohol free beers is reported to influence the level of the final arsenic species found in beer. Monomethylarsonic acid is the most abundant species in alcoholic beers, while inorganic arsenic (III) is similar to the organic species in alcohol free beers 22 . Furthermore in 2002, the Bundesamt für Verbraucherschutz und Lebensmittelsicherheit 5 reported an average arsenic content of 7.4 μg/L for the German market.…”
Section: Resultsmentioning
confidence: 99%
“…Genotypic variation in Cd concentration in grain has been reported in durum and bread wheat (Oliver et al, 1995;Li et al, 1997;Greger and Lofstedt, 2004); however, there are few data on the Cd concentration in grain in Japanese wheat cultivars. Evaluation of Cd concentration in grain in broad genetic resources is necessary to understand the mechanisms of grain Cd accumulation and to construct a breeding program to decrease the Cd concentration in grain in wheat.…”
mentioning
confidence: 99%
“…Thus, it is possible that Cl enhances the transfer of Cd from the root/shoot to the grain, in addition to increasing the solubility of soil Cd. Cd translocation from roots to shoots is considered to be important for the accumulation of Cd in wheat grain (Chan and Hale, 2004;Greger and Löfstedt, 2004;Harris and Taylor, 2004). Further studies are required to elucidate the mechanisms underlying the effects of Cl on grain Cd accumulation.…”
Section: Discussionmentioning
confidence: 99%